Improving understanding and utilization of the antibiogram among medical residents - Stephen J. Cooper; Christopher J. Destache; Renuga Vivekanandan (Cambridge University Press, 2022)
In this quality improvement project, we sought to increase the understanding and utilization of the antibiogram among physicians in family medicine, internal medicine, and surgery residency programs at a Midwest Academic Healthcare institution. Through simple, inexpensive measures the comfort with, access to, and utilization of the antibiogram can be improved.